2015
DOI: 10.1039/c5ra12852h
|View full text |Cite
|
Sign up to set email alerts
|

Improving photocatalytic activity by combining upconversion nanocrystals and Mo-doping: a case study on β-NaLuF4:Gd,Yb,Tm@SiO2@TiO2:Mo

Abstract: A novel double-shell-structured β-NaLuF 4 : Gd,Yb,Tm@SiO 2 @TiO 2 :Mo nanocomposite photocatalyst has been developed for the first time. The nanocomposite consists of uniform β-NaLuF 4 : Gd, Yb, Tm upconversion nanocrystals as core, a media shell of SiO 2 , and a lot of small sized anatase TiO 2 nanoparticles as the outer shell. The TiO 2 shell is modified by Mo-doping, which can narrow the band-gap of TiO 2 and act as electron traps resulting in enhancement of light absorption and reduction of recombination r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…27-0726). 25 Highresolution transmission electron microscopy (HRTEM) images revealed the single crystalline attribute, as corroborated by the observed clear lattice fringes with the measured d spacing (0.528 nm), consistent with the lattice spacing of the (100) plane of NaLuF 4 (JCPDS no. 27-0726).…”
Section: ■ Results and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…27-0726). 25 Highresolution transmission electron microscopy (HRTEM) images revealed the single crystalline attribute, as corroborated by the observed clear lattice fringes with the measured d spacing (0.528 nm), consistent with the lattice spacing of the (100) plane of NaLuF 4 (JCPDS no. 27-0726).…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…The powder X-ray diffraction (XRD) pattern showed that as-synthesized U was of a hexagonal phase (Figure S1a), which matched with β-NaLuF 4 (JCPDS no. 27-0726) . High-resolution transmission electron microscopy (HRTEM) images revealed the single crystalline attribute, as corroborated by the observed clear lattice fringes with the measured d spacing (0.528 nm), consistent with the lattice spacing of the (100) plane of NaLuF 4 (JCPDS no.…”
Section: Resultssupporting
confidence: 67%
“…Considering the non-linearity of this effect, up-conversion enhanced photocatalysis has only been demonstrated with a relatively high excitation provided by an infrared laser. [9][10][11][12][13][14][15] Nevertheless, we demonstrated previously that up-converting NaGdF 4 :Yb 3+ ,Tm 3+ nanocrystals can also enhance photocatalysis under solar irradiation. 16 This last result was counter-intuitive if one considers that the addition of the energy of at least 3 photons in the IR are required to obtain one excitation in the UV.…”
mentioning
confidence: 88%
“…Using upconversion materials to convert many more solar spectrum photons into useful ones could greatly enhance the production rate, provided that they demonstrate the ability to produce UV photons. Considering the nonlinearity of this effect, upconversion-enhanced photocatalysis has only been demonstrated with a relatively high excitation provided by an infrared laser. Nevertheless, we demonstrated previously that upconverting NaGdF 4 :Yb 3+ ,Tm 3+ nanocrystals can also enhance photocatalysis under solar irradiation . This last result was counterintuitive if one considers that the addition of the energy of at least 3 photons in the IR is required to obtain one excitation in the UV.…”
mentioning
confidence: 95%
“…Super hydrophilic surface acts as selfcleaning with water contact angle less than 50 o , which is necessary for a droplet to roll off the surface [3]. Meanwhile, photocatalysis refers a chemical reaction between organic species and free radicals upon irradiation with UV-visible or near-infrared (NIR) light that degrades the harmful pollutant on the glass surface [4]. Among various photocatalysts, titania nanoparticles (TiNPs) are frequently used for self-cleaning purpose due to its strong photocatalytic properties which able to decompose common dye pollutants such as Methylene Blue (MB) [2].…”
Section: Introductionmentioning
confidence: 99%